Perspectives on Contributory Factors to Student Success in Higher Education at a University in South Africa - Peter Sabelo; Dagogo William Legg-Jack (E-Journal of Humanities, Arts and Social Sciences, 2022)
Over time, many students that enroll in programmes at the university end up dropping out without completing their studies. This trend is worrisome as it points to a defeat of the objectives of entering and graduating from the university. Therefore, this study explored the perspectives of contributory factors to student success in higher education at a South African University. The study addressed one objective namely, participants’ understanding of factors that contribute to student success in higher education. To address this objective, a qualitative case study design located in the interpretive paradigm was employed to generate data through a semi-structured interview from twelve participants purposively selected from undergraduate and postgraduate students. Of these twelve participants, four represented First Time Entering (FTEN) students, four (4) second year and third year respectively and four (4) postgraduate students across two faculties, namely the Faculty of Education and School Development and Faculty of Economics and Information Technology Systems , Komani campus,Walter Sisulu University, South Africa. The data was analysed thematically. The results revealed the following themes, namely, no student left behind, the need for an enabling environment, students as partners, data-informed practices, assessment for sustainability, and a multi-dimensional approach for success. With these findings, the study concludes that addressing the needs of all students collectively, creating an enabling environment, involving students as partners, the use of data-informed practices, and assessment for sustainability among others all impact students’ success in higher education. Thus, as part of the contribution to the body of knowledge, these findings highlight factors that contribute to the debate on students’ success in higher education.